Frame body structure for solar car - Muhamad Izwan, Sunawan (2010)
This report presents about the frame design structure for solar car. Solar car has been invented to find an alternative energy that can be replaced the common energy that being used right now which is fuel energy. The condition to design for this frame design is lightweight in term of weight, low displacement on frame when accident due to tensile strength of the material and the high natural frequency of that design. Objective of this report is to create a preliminary study for possible design of solar car frame.A researchabout solar car frame design is conducted to see whether the solution for the parameter can be obtained from the journal, technical paper and also the research about solar car system. The answers from the design will be analysed in order to choose the best model and features of the three wheel solar car frame design. The design of the final model will be done by using SolidWork software which is suitable for making the 3D model of the car. Then the design will included into ALGOR software to analyse about natural frequency and also the roll bar testing and got the results that the third chassis of the solar car is the best chassis that can be use inside the solar car to optimize the solar energy used